Water‐soluble metalated and non‐metalated A2B‐ and A3‐corrole/amino acid conjugates: syntheses, characterization and properties. (10th June 2013) - Schmidlehner, Melanie; Faschinger, Felix; Reith, Lorenz Michael; Ertl, Martin; Schoefberger, Wolfgang
Abstract : In this study, novel water‐soluble corrole amino acid conjugates were synthesized and characterized. Thecoupling reaction of A2 B‐ and A3 ‐corroles with glycine ethyl ester and taurine under strong basic conditions proved to be successful and yielded di‐ and trifunctionalized corrole amino acid conjugates in good yields. The subsequentmetalation of the corrole/amino acid conjugates broadens the scope for applications considerably. As examples, we herein show thecatalytic activity of the Mn(III) A3 ‐corrole towards O2 evolution. First we employed tert ‐butyl hydroperoxide ( t ‐BuOOH) as oxidant to obtain the Mn(V)oxo species and tetrabutyl ammonium hydroxide (TBAH) as hydroxide donor agent. Furthermore, the binding properties of the non‐metalated and the Mn(III) A3 ‐corrole/amino sulfonic acid conjugates and transport of proteins were investigated and the conjugates exhibited binding to human serum albumin (HSA). Finally, a novel Ga(III) A3 ‐corrole/amino sulfonic acid derivative was synthesized and we briefly describe the photophysical properties of this compound. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : In this study, novel corrole amino acid conjugates were synthesized and characterized. The coupling reaction of tris‐pentafluorophenyl corrole H3 (TFPC) with glycine ethylester and 2‐aminoethanesulfonic acid under strong basic conditions proved to be successful and yielded water soluble tri‐functionalized corrole amino acid conjugates in good yields. Subsequent metalation procedures with GaCl3 and Mn(OAc)2 succeeded with high yields. The luminescent properties of the Ga +III corroles complex and the oxygen evolution properties as well as the protein binding properties of the Mn +III/+V corrole complexes were evaluated in aqueous solutions.